Photodegradation of chlorbromuron, atrazine, and alachlor in aqueous systems under solar irradiation - Cristina Lizama Bahena; Susana Silva Martínez (International Journal of Photoenergy)
Homogeneous and heterogeneous aqueous systems of the herbicides of chlorbromuron, atrazine, and alachlor were irradiated with a nonexpensive solar irradiation using a photoreactor with recirculation. Photodegradation of these herbicides occurred in both aqueous systems; however the presence of TiO2 clearly accelerated the degradation of the three herbicides in comparison with direct photolysis. Degradation was followed by measuring the chemical oxygen demand (COD) as a function of reaction time for each aqueous system. Over 90% of COD abatement in the heterogeneous aqueous system was obtained in a short time period showing that mineralization of chlorbromuron, atrazine, and alachlor was achieved.